Secretion of a lysophospholipase D activity by adipocytes: involvement in lysophosphatidic acid synthesis - Gesta, Stéphane (Federation Of American Societies For Experimental Biology, 2002)
The aim of the present work was to depict the metabolic pathways involved in extra-cellular production of lysophosphatidic acid (LPA) by adipocytes. LPA was followed by quantifying the accumulation of LPA in the incubation medium (conditioned medium: CM) of 3T3F442A adipocytes, or human adipose tissue explants, using a radioenzymatic assay. Surprisingly, after separation from the cells, the amount of LPA present in CM could significantly be increased by further incubation at 37°C. This suggested the presence of a LPA-synthesizing activity (LPA-SA) in CM. LPA-SA appeared as a soluble activity which was inhibited by divalent ion chelators: EDTA and phenanthrolin. The effect of EDTA was preferentially reverted by CoCl2, as described for a lysophospholipase D- (lyso-PLD) activity previously identified in rat plasma. LPA concentration could also be increased by treatment with a bacterial PLD, demonstrating the presence of PLD-sensitive LPA-precursors (mainly lysophosphatidylcholine) in adipocyte CM. LPA-SA could be increased by addition of exogenous lysophosphatidylcholine, lysophosphatidylglycerol, or lyso-platelet activating factor, demonstrating that LPA-SA resulted from the action of a lyso-PLD. LPA-SA was not inhibited, but rather activated, by primary alcohol (ethanol and 1-butanol), suggesting that adipocyte lyso-PLD was not a classical PLD. Finally, LPA-SA was found to be weaker in CM of undifferentiated adipocyte (preadipocytes) as compared to CM of differentiated adipocytes. In conclusion, our results reveal the existence of a secreted lyso-PLD activity regulated during adipocyte-differentiation and involved in extra-cellular production of synthesis of LPA by adipocytes.